Human Major Histocompatibility Complex (MHC) Class I Molecules with Disulfide Traps Secure Disease-related Antigenic Peptides and Exclude Competitor Peptides - Truscott, Steven M. (American Society for Biochemistry and Molecular Biology, 2008)
The ongoing discovery of disease-associated epitopes detected by CD8 T cells greatly facilitates peptide-based vaccine approaches and the construction of multimeric soluble recombinant proteins (e.g. tetramers) for isolation and enumeration of antigen-specific CD8 T cells. Related to these outcomes of epitope discovery is the recent demonstration that MHC class I/peptide complexes can be expressed as single chain trimers (SCTs) with peptide, β(2)m and heavy chain connected by linkers to form a single polypeptide chain. Studies using clinically relevant mouse models of human disease have shown that SCTs expressed by DNA vaccination are potent stimulators of cytotoxic T lymphocytes. Their vaccine efficacy has been attributed to the fact that SCTs contain a preprocessed and preloaded peptide that is stably displayed on the cell surface. Although SCTs of HLA class I/peptide complexes have been previously reported, they have not been characterized for biochemical stability or susceptibility to exogenous peptide binding. Here we demonstrate that human SCTs remain almost exclusively intact when expressed in cells and can incorporate a disulfide trap that dramatically excludes the binding of exogenous peptides. The mechanistic and practical applications of these findings for vaccine development and T cell isolation/enumeration are discussed.